Selenogonus narinoensis Stirton, 1947 (Tayassuidae, Cetartiodactyla, Mammalia): taxonomic status and paleobiogeographic implications - Gasparini, Germán Mariano (2021)
The species Selenogonus narinoensis was described by Stirton (1947) based on a single; specimen which comes from sediments cropping out in the Cocha Verde; locality, Narino Department (Colombia), tentatively referred to the late; Pliocene–Pleistocene (MGN 931; IGM p002118, Museo Geologico Nacional,; Servicio Geologico Colombiano, Bogota). However, morphological; studies and comparative morphometric observations of the specimen suggest; that (1) no diagnostic character supports the validity of the species; Selenogonus narinoensis (here considered species inquirenda); (2) a combination of features (e.g., the mandibular condyle; located behind the posterior edge of the vertical mandibular ramus, the; angular process which projects laterally outwards, a bunolophodont crown; morphology, a mesodont crown height, and a simple crown morphology of the; third lobe of m3) indicates it belongs to the genus Platygonus; (3) this specimen; corresponds to one of the largest South American peccaries; (4) taking into; account certain anatomical characters as well as its morphometric range,; this specimen is assigned to Platygonus cf. marplatensis. Even though the stratigraphic provenance of; the specimen is still doubtful, it can be proposed that (1) it could be one; of the most ancient records of tayassuids in South America, as would be; expected given its geographical position, and (2) considering the new taxonomic; proposal, this specimen represents the first record of Platygonus cf. marplatensis in Colombia and; represents one of the northernmost South American records of the genus. This; new interpretation would be of great relevance in the Great American Biotic; Interchange due to its strategic geographical proximity to the Isthmus of Panama.